If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2p + 2) + -10 = 7 + -10p Reorder the terms: -1(2 + 2p) + -10 = 7 + -10p (2 * -1 + 2p * -1) + -10 = 7 + -10p (-2 + -2p) + -10 = 7 + -10p Reorder the terms: -2 + -10 + -2p = 7 + -10p Combine like terms: -2 + -10 = -12 -12 + -2p = 7 + -10p Solving -12 + -2p = 7 + -10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '10p' to each side of the equation. -12 + -2p + 10p = 7 + -10p + 10p Combine like terms: -2p + 10p = 8p -12 + 8p = 7 + -10p + 10p Combine like terms: -10p + 10p = 0 -12 + 8p = 7 + 0 -12 + 8p = 7 Add '12' to each side of the equation. -12 + 12 + 8p = 7 + 12 Combine like terms: -12 + 12 = 0 0 + 8p = 7 + 12 8p = 7 + 12 Combine like terms: 7 + 12 = 19 8p = 19 Divide each side by '8'. p = 2.375 Simplifying p = 2.375
| 7xy^2-9+21x-3y^2= | | 3-6x=5x+18 | | -5(10n+3)=-(4-9n) | | -9=-(3+2)-32 | | 3/8-(-1/12) | | X+(-x+11)=2+(4x+3) | | -(-p+2)=3(1+6p) | | 400=5wh | | -(8x+1)-4=5+8x | | m+13=8 | | 0.6(5x+10)=1.1-(x+2) | | 2u-4=-12 | | -(k+1)=5k+5 | | -2q-(9-q)=-5 | | .33(9-3x)=2 | | 3(9x+1)=-8x+4 | | 3g^2+8g-3=0 | | 21x^5+14x^3+35x= | | -8x^2-6x+5=0 | | 4x+4/8-12y | | 7t-4(3-4t)=-5 | | -(2z+1)=-3(-9-8z) | | 6x+26=13x-51 | | -(-3y+1)8=1+4y | | -x+2=-11 | | 3(n-4)=36 | | 15/13-3 | | 7t-(-2-6t)=1 | | 4x-3(2x+6)=-(2x-5) | | -2+k=-(3k+3) | | 1x+4x+7x=180 | | 12-(-2)/7+(-3)+(2)(-9) |